Vicente Ximenes, LBJ's Great Society, and Mexican American civil rights rhetoric - Kells, Michelle Hall (Southern Illinois University Press, 2018)
Beginning as a grassroots organizer in the 1950s, Vicente Ximenes was at the forefront of the movement for Mexican American civil rights through three presidential administrations, joining Lyndon B. Johnson's Great Society and later emerging as one of the highest-ranking appointees in Johnson's administration. Ximenes succeeded largely because he could adapt his rhetoric for different audiences in his speeches and writings. Michelle Hall Kells elucidates Ximenes's achievements through a rhetorical history of his career as an activist. Kells draws on Ximenes's extensive archive of speeches, reports, articles, and oral interviews to present the activist's rhetorical history. After a discussion of Ximenes's early life, the author focuses on his career as an activist, examining Ximenes's leadership in several key civil rights events, including the historic 1967 White House Cabinet Committee Hearings on Mexican American Affairs. Also highlighted is his role in advancing Mexican Americans and Latinos from social marginalization to greater representation in national politics. This book shows us a remarkable man who dedicated the majority of his life to public service, using rhetoric to mobilize activists for change to secure civil rights advances for his fellow Mexican Americans.